2020
DOI: 10.1002/ange.202003105
|View full text |Cite
|
Sign up to set email alerts
|

A Glycan Array‐Based Assay for the Identification and Characterization of Plant Glycosyltransferases

Abstract: Growing plants with modified cell wall compositions is a promising strategy to improve resistance to pathogens, increase biomass digestibility, and tune other important properties. In order to alter biomass architecture, a detailed knowledge of cell wall structure and biosynthesis is a prerequisite. We report here a glycan array‐based assay for the high‐throughput identification and characterization of plant cell wall biosynthetic glycosyltransferases (GTs). We demonstrate that different heterologously express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The Arabidopsis genes At1G77810 (Qu et al ., 2008), At1G33430 (called UPEX1 or KNS4; Suzuki et al ., 2017) as well as GALT8 (Narciso et al ., 2021) belonging to clade II and possibly CAGE1 and CAGE2 (clade I, Nibbering et al ., 2022) encode β-1,3-galactosyltransferases which function in AGP β-1,3-galactan backbone synthesis. Galactan side chains of AGPs consisting of β-1,6-linked Gal are synthesized by β-1,6-galactosyltransferases of family GALT31A (clade II, Geshi et al ., 2013), although in a recent study GALT31A was found to galactosylate substituted and unsubstituted β-1,3-galactan oligosaccharides rather than β-1,6-linked galactan oligosaccharides (Ruprecht et al ., 2020). Homologs to sequences from all Arabidopsis enzymes from group A and B responsible for synthesis of the galactan structure are present in Azolla , Salvinia , Ceratopteris and all investigated fern transcriptomes.…”
Section: Resultsmentioning
confidence: 98%
“…The Arabidopsis genes At1G77810 (Qu et al ., 2008), At1G33430 (called UPEX1 or KNS4; Suzuki et al ., 2017) as well as GALT8 (Narciso et al ., 2021) belonging to clade II and possibly CAGE1 and CAGE2 (clade I, Nibbering et al ., 2022) encode β-1,3-galactosyltransferases which function in AGP β-1,3-galactan backbone synthesis. Galactan side chains of AGPs consisting of β-1,6-linked Gal are synthesized by β-1,6-galactosyltransferases of family GALT31A (clade II, Geshi et al ., 2013), although in a recent study GALT31A was found to galactosylate substituted and unsubstituted β-1,3-galactan oligosaccharides rather than β-1,6-linked galactan oligosaccharides (Ruprecht et al ., 2020). Homologs to sequences from all Arabidopsis enzymes from group A and B responsible for synthesis of the galactan structure are present in Azolla , Salvinia , Ceratopteris and all investigated fern transcriptomes.…”
Section: Resultsmentioning
confidence: 98%
“…The A. thaliana GT31 enzymes from clade IV have not been characterized, but cotton orthologs suggest that clade IV possesses β‐1,3‐galactosyltransferase activity (Qin et al., 2017). The enzyme GALT31A (clade II) was initially characterized to have β‐1,6‐galactosyltransferase activity (Geshi et al., 2013), although a recent study indicated that it is actually a β‐1,3‐galactosyltransferase (Ruprecht et al., 2020). Mutations in Arabidopsis GALT31A were found to arrest embryonic development at the globular stage, which indicates that this protein and the β‐1,3‐galactan linkages it catalyzes are crucial in plants (Geshi et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The A. thaliana GT31 enzymes from clade IV have not been characterized, but cotton orthologs suggest that clade IV possesses b-1,3-galactosyltransferase activity (Qin et al, 2017). The enzyme GALT31A (clade II) was initially characterized to have b-1,6galactosyltransferase activity (Geshi et al, 2013), although a recent study indicated that it is actually a b-1,3galactosyltransferase (Ruprecht et al, 2020) crucial in plants (Geshi et al, 2013). A close clade II homolog of GT31A called KAONASHI4 (KNS4) was also shown to be a b-1,3-galactosyltransferase, with kns4 mutants displaying reduced fertility, shorter seed pods and reduced seed set as a result of defects in pollen exine development (Suzuki et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently introduced a plant glycan microarray, which enabled us to determine the acceptor substrate specificities of plant glycosyltransferases and the epitopes of a large number of cell wall glycan‐directed antibodies [20] . This array consists mostly of synthetic plant cell wall‐derived oligosaccharides and is constantly further developed [21] . To procure fungal oligosaccharides for investigating plant‐activatory molecules and the corresponding receptors, we applied recently developed methodologies in automated glycan assembly (AGA) [22] and 1,2‐ cis ‐selective glucan synthesis [23] .…”
Section: Introductionmentioning
confidence: 99%
“…[20] This array consists mostly of synthetic plant cell wall-derived oligosaccharides and is constantly further developed. [21] To procure fungal oligosaccharides for investigating plant-activatory molecules and the corresponding receptors, we applied recently developed methodologies in automated glycan assembly (AGA) [22] and 1,2-cis-selective glucan synthesis. [23] In total, we synthesized twelve oligosaccharides including chito-, β-(1!6)-gluco-, α-(1!…”
Section: Introductionmentioning
confidence: 99%